Importance of Genetic Diagnostics in Adult-Onset Focal Segmental Glomerulosclerosis - Snoek, Rozemarijn (Nephron Clin Pract, 2019)
Focal segmental glomerulosclerosis (FSGS) is a histological pattern of podocyte and glomerulus injury. FSGS can be primary and secondary to other diseases or due to a genetic cause. Strikingly, genetic causes for adult-onset FSGS are often overlooked, likely because identifying patients with genetic forms of FSGS based on clinical presentation and histopathology is difficult. Yet diagnosing genetic FSGS does not only have implications for prognostication and therapy but also for family and family planning. In this case series, we present 3 adult patients who presented with advanced renal disease with the histological picture of FSGS and proved to have a genetic cause of the disease, namely, variants in INF2, COL4A4 and HNF1B, respectively. We show the possibilities of identifying genetic FSGS based on clinical clues of a positive family history, early age at onset of disease, and/or severe therapy-resistant disease. We discuss ways to select the method of genetic testing for individual patients. Finally, we examine how the judicious use of genetic investigations can obviate potential harmful diagnostic procedures and direct clinical decisions in patients and their relatives.